Does Tribulus terrestris improve toxic effect of Malathion on male reproductive parameters? - Mohammad Reza Salahshoor; Amir Abdolmaleki; Azita Faramarzi; Cyrus Jalili; Roshankhah Shiva (Wolters Kluwer Medknow Publications, 2020)
Background: Tribulus terrestris has antioxidant and free-radical-scavenging properties. Malathion is the most common organophosphate, which is capable to produce free radicals and induce disturbance on some of male reproductive parameters. This study was designed to evaluate the effects of T. terrestris extract against damage induced by Malathion to the reproductive parameter of male rats. Materials and Methods: In this experimental study, 48 male Wistar rats were randomly assigned to eight groups: first group, sham group (normal saline); second group, Malathion (250 mg/kg) group; third to fifth groups, T. terrestris groups (2.5, 5, and 10 mg/kg body weight, respectively); and sixth to eight groups, Malathion + T. terrestris groups (2.5, 5, and 10 mg/kg). Tribulus terrestris extract (2.5, 5, and 10 mg/kg body weight, respectively) administrated orally, and daily for 8 weeks. The sperm parameters, testis malondialdehyde (MDA), serum total antioxidant capacity, serum testosterone level, and the height of germinal layer were evaluated and analyzed statistically. Results: All the values of male reproductive parameters reduced significantly in the Malathion group as compared to the sham group (P < 0.01) except MDA level, which increased significantly. The T. terrestris and T. terrestris + Malathion treatments in all doses increased the whole parameters significantly as compared to the Malathion group (P < 0.01) except MDA level, which decreased significantly. No significant changes were observed in all T. terrestris groups as compared to the sham group (P > 0.05). Conclusion: Tribulus terrestris extract administration attenuates the toxic effects of Malathion on some of the male reproductive parameters.